The Effectiveness of a Pelican Crossing as Effort to Fulfill The Right to Security of The Person Based From The Citizenship Perspective's Review - Juang Pratama Abdi; Cecep Darmawan (Department of Civic Education, 2021)
Fulfillment the right to security of the person is one of the human rights according to Law of the Republic of Indonesia No. 39 of 1999 on Human Rights. Dinas Perhubungan Kota Bandung is a public institution has the main task of service in the field of transportation. One of the efforts the main tasks and service functions is provide Pelican Crossing’ policy in every corner of the city of Bandung. The purpose of this research is find out how effective the implementation of the Pelican Crossing with a specific to knowing and analyzing the planning, implementation, and evaluation of the Pelican Crossing’s implementation. This research uses a qualitative approach with a case study method. Data collection techniques used interview, observation, and documentation studies. The participants in this study were the Kasi Perlengkapan Jalan Dinas Perhubungan Kota Bandung, members of Satlantas Polrestabes Kota bandung, and the Pelican Crossing users. The results are; 1) The planning process of the Pelican Crossing; 2) Implementation of the Pelican Crossing; 3) The effectiveness of the Pelican Crossing as an effort to fulfill the right to security of the Bandung citizens; and 4) Constraints and solutions for the implementation of Pelican Crossing in Bandung City